(untitled) (Journal of Management and Social Sciences, 2018)
Museums have been established as a veritable instrument for a virile tourism industry because of advantages inherent in them. Their potentials for showcasing the people and their culture is also a case that cannot be ignored. For the purpose of clarity, this paper highlights the historical antecedents of museums in Nigeria with a view to helping in the understanding of museum as a concept and that it is not alien to indigenous African societies before the advent of the Europeans. It traces the development of modern museums in the colonial period, up to the present and notes the problems and associated difficulties attached to the effective management and funding of museums in Nigeria. Specifically, the paper investigates the community knowledge and attitude towards Museums and its implication on sustainable livelihood in Ile-Ife City, with particular focus on Ife National Museum. The study made use of questionnaire and indepth interview to collect data from the study population. A total of 180 copies of questionnaire were retrieved from the respondents and analysed. The findings revealed a high level of awareness about the existence of Museums among the people and a low level of patronage for leisure and tourism purposes, which implies poor appreciation of its social and health benefits. This poor patronage was traced to poor appreciation of culture, which inherently has implication on sustainable livelihood and developmental processes. The need to address this consequently becomes apt in view of empirical declaration that existing models of sustainable development forged from economic or environmental concern are unlikely to be successful without cultural considerations. Keywords Museums, knowledge, attitude, sustainable livelihood